Isolation and Characterization of the Microbiological and Physicochemical Qualities, the Protein and Amino Acid Profiles of Fermented Chicken and Duck Egg Ovalbumin - Nurliyani; Abidin, M. Z.; Kandarina, I. (Faculty of Animal Science, IPB University, 2025)
The objective of this study was to isolate and characterize the microbiological and physicochemical qualities, and the protein and amino acid profiles of fermented chicken and duck egg ovalbumin (OVA). The OVA was fermented using lactic acid bacteria (LAB) Lactobacillus paracasei M104 taken from goat milk and yeast Kluyveromyces marxianus KFA9 obtained from kefir. The OVA and fermented OVA were characterized by analyzing its electrophoresis and spectral profile on FTIR, amino acid profile, and microbiological and physicochemical properties. The findings indicated that the chicken and duck OVA showed a molecular weight between 45-55 kDa. The amount of LAB in OVA before and after fermentation was not significantly different. However, the amount of yeast decreased after fermentation. The concentrations of soluble protein, total free amino acids, and alcohol in the fermented chicken OVA were higher than those in fermented duck OVA. The OVA of chicken and duck eggs showed a comparable pattern in specific bands within the FTIR spectrum. However, there were several different bands in the FTIR spectra between OVA and fermented OVA. Specific carbohydrate-containing bands were notably absent in the fermented OVA. After fermentation, the chicken OVA indicated an increase in all types of amino acid concentrations. Conversely, the amino acid concentrations were constant before and after fermentation in duck OVA. The changes in the secondary structure of protein may affect its functional characteristics, which needs further studies. It is expected that fermented OVA produced using local starters can be used as an ingredient in functional foods.